Kajian evaluasi budaya organisasi Perpustakaan Nasional Republik Indonesia - Salahudin, Salahudin; Nurmandi, Achmad; Santoso, Joko; Kusumawardhani, Budi; Rusdianto, Rusdianto; Agusta, Rendra; Loilatu, Mohammad Jafar (Perpustakaan Universitas Gadjah Mada, 2020)
Introduction. This study aims to determine the organizational culture in the National Library of Indonesia (NLI) based on several aspects including clan (human resource management), adhocracy (innovation organization), market (adaptation and strategic organization), and hierarchy (coordination and organizational structure). Research Methods. This study used a quantitative approach of Competing Values ​​Framework (CVF) developed by Cameron & Quinn (2011) to obtain data scores and the average of each aspect of organizational culture. Data Analysis. Organizational Culture Assessment Instrument (OCAI) is an organizational culture assessment instrument by using statements/questions relating to the six subsystems, namely organizational culture dominant characters, leadership, human resource management, internal solidarity, strategic management and organizational success criteria. The data was analysed by using SPSS with Pearson Correlation formula. Results and Discussion. We found that organizational culture of the National Library is cultural hierarchy. Conclusion and Recommendations. Organization culture of the (NLI) shows the cultural hierarchy. The cultural hierarchy is maintained as part of the working principles of the organization.